Analisis Fundamental Makro, Fundamental Mikro, Struktur Kepemilikan, Kinerja Keuangan, Karakteristik Terhadap Nilai Perusahaan Sebagai Variable Modetaring pada Perusahaan Sektor Makanan dan Minuman yang Terdaftar di BEI Periode 2018-2023 - Wardana, Muhammad Indra; Hwihanus (LANCAH: Jurnal Inovasi dan Tren, 2024)
This study aims to test and analyse the effect of macro fundamentals, micro fundamentals, ownership structure, financial performance, company characteristics, on firm value in food and beverage sector manufacturing companies listed on the Indonesia Stock Exchange (IDX). The method used in this study involves collecting data from six food and beverage sector manufacturing companies listed on the Indonesia Stock Exchange (IDX), namely such as PT Indofood Sukses Makmur Tbk, PT Mayora Indah Tbk, PT Ultrajaya Milk Industri Company Tbk, PT Nippon Indosari Corporindo Tbk, PT Siantar Top Tbk, PT Sariguna Primatirta. This research uses a quantitative approach and then analyses the data using Structural Equation Modeling (SEM) with the Partial Least Square (PLS) approach. SEM-PLS was chosen because it is able to test complex research models with multiple variables and indicators (Hair et al., 2014). SEM-PLS analysis was carried out using SmartPLS 4.0 software. The results of the study showed that of the 11 hypothesis results made, 4 hypotheses were significantly accepted and 7 hypotheses were rejected as insignificant.